Pengaruh Model Cooperative Learning Tipe NHT terhadap Hasil Belajar Luas Trapesium dan Layang-layang - Zulfaneri, Rahayu; Masniladevi, Masniladevi; Mahyuddin, Ritawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of learning with the Cooperative Learning Model Type NHT on the learning outcomes of broad trapezoidal and kite. This type of research is quantitative research with experimental methods, with a quasi experimental design with the form of a pretest-posttest non-euivalent group. The results showed that the average value of the pretest of the experimental group was 55.4 and the control group was 57.8. Analysis of the two groups using the t-test, obtained results of tcount of -6.382 and ttable at the 0.05 significance level of 2.024, so that tcount < ttable. While the average posttest value of the experimental group was 79.6 and the control group was 65.8. Analysis of the two groups using the t-test, obtained results of tcount of 4.0588 and ttabel at the 0.05 significance level of 2.024, so that tcount > t table. This shows that there are influences on the broad learning outcomes of trapezoidal and kites using the NHT type cooperative learning model.                                                                   Keywords : NHT Model, Learning Outcomes